Academic Resilience of High School Students Based on Gender Types at Limited Face to Face Learning Time - Faturrohmah, Afi; Sagita, Dony Darma (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2023)
Academic resilience is the resilience of a student that allows him to bear all academic burdens and adapt to a new way of learning because by becoming a resident student it will have influence to keep and make better student welfare, including learning in the Covid-19 pandemic situation. The purpose of this study was to provide an overview of the academic residency of the students of state junior high school 130 Jakarta during the Limited Face-to-Face Learning period based on gender. Measurement of academic resiliency level in this research using resiliency dimensions measured by the adaptation results of the Adaptation Factor Analysis of Academic Resilience Instruments Version Indonesia: Exploratory and Confirmatory Approaches using quantitative methods. The sample used was 290 students of SMPN 130 Jakarta with descriptive analysis techniques found that the average academic residency of SMPN 130 Jakarta students was 90.01 which can be categorized as moderate and there is a no difference between the academic residency rate of female students and male students.